2007
DOI: 10.1111/j.1472-765x.2007.02127.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Escherichia coli and Listeria monocytogenes on iceberg lettuce by dip wash treatments with organic acids

Abstract: Aims:  To study and compare the efficacy of organic acids and chlorine dipping in inactivation of Escherichia coli and Listeria monocytogenes on fresh‐cut iceberg lettuce. Methods and Results:  Fresh‐cut iceberg lettuce leaves were inoculated with E. coli or L. monocytogenes. After inoculation, samples were stored at 4°C for 24 h and dipped in organic acid or chlorine solutions for 2 and 5 min. E. coli and L. monocytogenes were enumerated on selective media. Treatment of fresh‐cut iceberg lettuce with chlorine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
109
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(119 citation statements)
references
References 25 publications
8
109
0
2
Order By: Relevance
“…According to Parish et al, (2003), efficacy of treatment depends on Physiology of target microorganism, characteristic of produce surface, exposure time and concentration of sanitizer. The results of this research are in line with the findings of Amoah et al, (2009);Akbas and Olmez (2007) which demonstrated that dipping lettuce in 0.5% lactic and citric acid for 2mins was effective in reducing the microbial population, prior to consumption.…”
Section: Discussionsupporting
confidence: 82%
“…According to Parish et al, (2003), efficacy of treatment depends on Physiology of target microorganism, characteristic of produce surface, exposure time and concentration of sanitizer. The results of this research are in line with the findings of Amoah et al, (2009);Akbas and Olmez (2007) which demonstrated that dipping lettuce in 0.5% lactic and citric acid for 2mins was effective in reducing the microbial population, prior to consumption.…”
Section: Discussionsupporting
confidence: 82%
“…This indicates that washing for 1 minute would be sufficient to reduce pathogen populations on leafy greens such as baby and mature spinach, and iceberg lettuce. Our results are similar to those obtained by Akbas and Ölmez [26] where no significant differences were observed between treatment times (2 and 5 minutes) to reduce E. coli on iceberg lettuce on day 0. Lin et al [23] also demonstrated that increasing hydrogenperoxide exposure time from 60 seconds to 90 seconds did not significantly affect S. Enteritis, L. monocytogenes and E. coli O157:H7 populations on lettuce leaves on day 0.…”
Section: Discussionsupporting
confidence: 81%
“…It was reported that selected house-hold vinegars with concentration of 2.5 and 5% acetic acids were effective in inhibition against L. monocytogenes, E. coli O157:H7, and S. Typhimurium however, only 5% vinegar was effective against S. Typhimurium (Yang, Kendall, Medeiros, & Sofos, 2009). Reduction of L. monocytogenes and pathogens after dipping/spraying or in combination with organic acid solutions has been reported in several studies (Akbas & Olmez, 2007;Nastou et al, 2012). This study investigated the efficacy of dipping/shaking at room temperature with different natural washing solutions containing organic acids in combination with origanum oil and how these solutions reduced micro-organisms in the fresh produce under examination.…”
Section: Decontamination Of Foodborne Pathogenmentioning
confidence: 99%